Immunochemistry and Molecular Approaches towards Identification of Malaysian Cyprinid Herpesvirus - Soon, Samson Min Ngen (2001)
Immunochemistry and molecular approaches were used to identify a Malaysian cyprinid herpesvirus responsible for papilloma among Koi carps (Cyprinus carpio L.) and goldfish (Carassius auratus L.) in Malaysia. Immunochemistry approaches employing hybridoma technology established a hybridoma clone (DG3-1) producing specific IgM K light chain monoclonal antibody (MAb) against Malaysian cyrprinid herpesvirus. The MAb was cross-reactive against Japanese cyprinid herpesvirus type 1 (CHV) antigens but not against Channel catfish herpesvirus (CCV) and Salmonid herpesvirus (SHV-2) in immunodot-blot assay. The cyprinid herpesvirus type-specific epitope recognised by the MAb was located on two viral polypeptides having the molecular weight of 58,000 and 67,000 daltons in Malaysian cyprinid herpesvirus and CHV through Western blot analysis. As the MAb showed no neutralization activity against virus infection in cell culture and glycosylation inhibitors did not affect the presence and migration of the antigens under polyacrylamide gel electrophoresis, evidences as such suggest the antigens are nonglycosylated components of the viral structure. Immunohistochemical analysis on goldfish papilloma tissue sections with MAb using labeled avidin binding (LAB) method demonstrated specific staining of cyprinid herpesvirus antigens within the nucleus of infected cells. Specific localization of these viral antigens in the cell nuclei were consistent with reports of nonglycosylated herpesvirus antigens involving viral capsid components or DNA-binding proteins. Employing molecular techniques, cyprinid herpesvirus nucleic acid sequences were later confirmed to be present in the immunohistochemical positive papilloma sections through in situ hybridization assay using a 1,161 bp CHV nucleic acid probe. Molecular identification by polymerase chain reaction (PCR) using CHV specific primers was extremely sensitive, specific, rapid and practical. The technique successfully amplified a 433 bp DNA fragment from frozen archival goldfish papilloma tissues and recent papillomas obtained from goldfish and carp hybrids. Nucleic acid sequencing of the DNA fragment revealed identical sequence homology with CHV, thus confirming conclusively that Malaysian cyprinid herpesvirus and CHV are members of the same group of virus. Detection sensitivity level as assessed with first step PCR, was capable of detecting viral nucleic acids from 1 fg or 200 copies of actual viral target sequences and from as low as 1-10 virus infected cells. Sensitivity level was increased 100-1000-fold when nested PCR strategy was employed. Specificity of detection evaluated by DNA fragment polymorphism demonstrated homologous DNA sequences among cyprinid herpesvirus representatives from Malaysia, Israel and Japan. A quantitative competitive PCR assay based on the current viral target sequence also provided quantitative description of infection and viral burden with preliminary results indicative of CHV possessing an alphaherpesvirus gene-like expression kinetics.